Calibration of WOFOST model for potato in India - Dua, V K; Govindakrishnan, PM; Singh, B P (Potato Journal, 2015)
A crop growth simulation model WOFOST was calibrated for four Indian potato cultivars, falling under different maturity classes i.e. late maturing (Kufri Badshah), medium maturing (Kufri Bahar and Kufri Jyoti) and early maturing (Kufri Pukhraj). The important model parameters used for calibration of WOFOST models were; thermal time from sowing to emergence, emergence to initiation of tuber growth and initiation of tuber growth to maturity, maximum leaf CO2 assimilation rate, initial light-use efficiency of CO2 assimilation of single leaf and dry matter partitioning. The model was calibrated for Indian potato cultivars with reasonable accuracy. Simulated values for emergence, initiation of tuber growth and physiological maturity varied between 0 to 2, 1 to 8 and 5 to 12 days, respectively, from the measured values, for different cultivars. Variation in final dry matter yield ranged from 5.6 to 7.5%, which was within the acceptable limits. The indicators of model performance also showed that the model performance was satisfactory. The results demonstrated that the WOFOST model can be used for potato crop under Indian situation. However model needs to be validated for various conditions before it is widely used.